Analisis Kesediaan Membayar (Willingness to Pay) Konsumen Terhadap Produk Kopi Berlabel Fairtrade di Berbagai Wilayah Indonesia - Ni Putu Ermina Saraswati; Mukson Mukson; Suryani Nurfadillah (University of Jember, 2023)
The increase in demand for coffee has not been in line with the increase in the welfare of the farmers. Fairtrade certification has a social premium for ensuring the welfare of farmers, but companies must anticipate higher production costs. This study aims to analyze the characteristics of consumers of coffee products in Indonesia, analyze the maximum WTP (Willingness to Pay) average value, and the factors that influence this value. This research was conducted in various regions in Indonesia with a sample of 218 respondents. Analysis was performed using descriptive analysis method, contingent valuation method (CVM) analysis, and multiple linear regression analysis. The results showed that the average coffee consumer was a woman aged 21-30 years, undergraduate education level, income less than IDR 2,000,000, bought 2-4 coffees per month, and had a moderate knowledge score. Respondents who were willing to pay more were 199 respondents with an average value of readiness to pay a maximum of IDR 4,909.55 and a total WTP aggregate value of IDR 977,000.00. Gender Factors, age, education level, income level, purchase quantity, attitude towards the environment, and lifestyle simultaneously influence the WTP value of Fairtrade coffee, while gender, knowledge, and lifestyle factors do not partially affect the WTP value of coffee Fairtrade label.